Evaluasi Penerimaan Generasi Z terhadap Chatbot Islami NURRA Menggunakan Technology Acceptance Model (TAM) - Salwa Aulia; Rizki Hikmawan; Raisyal Dimas Prayoga (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
This study evaluates the acceptance of the Islamic learning chatbot NURRA among Generation Z using the Technology Acceptance Model (TAM). It is motivated by the increasing consumption of digital religious information, which is not always accompanied by substantive understanding, thereby requiring interactive and adaptive learning media. A quantitative survey design was employed involving 30 Generation Z university students who had used NURRA for at least two weeks. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that perceived ease of use (PEOU), perceived usefulness (PU), and attitude toward use (ATU) were at high levels, with mean values of 4.342, 4.356, and 4.295, respectively. Structural analysis indicates that PEOU had a significant effect on PU (β = 0.751; p < 0.001) and ATU (β = 0.658; p = 0.003), whereas PU did not significantly affect ATU (β = 0.185; p = 0.420). These findings suggest that ease of use is the dominant factor in shaping user acceptance, while perceived usefulness is not yet strong enough to independently influence attitude toward use. Thus, the initial adoption of NURRA is driven more by ease of interaction than by perceived functional benefits. The findings imply the need to improve content quality so that NURRA becomes more credible and contextual for sustained use.